If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + 65x = 39x + 15 Reorder the terms: 3 + 65x = 15 + 39x Solving 3 + 65x = 15 + 39x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-39x' to each side of the equation. 3 + 65x + -39x = 15 + 39x + -39x Combine like terms: 65x + -39x = 26x 3 + 26x = 15 + 39x + -39x Combine like terms: 39x + -39x = 0 3 + 26x = 15 + 0 3 + 26x = 15 Add '-3' to each side of the equation. 3 + -3 + 26x = 15 + -3 Combine like terms: 3 + -3 = 0 0 + 26x = 15 + -3 26x = 15 + -3 Combine like terms: 15 + -3 = 12 26x = 12 Divide each side by '26'. x = 0.4615384615 Simplifying x = 0.4615384615
| 4e+x=8 | | C(x)=2.1x+3.2 | | 5x=-15x+4 | | Y=-0.25x^2+4 | | 0=x^2-40x+360 | | 0=x^2+40x+360 | | 10p+15q=5400 | | 560=8(n) | | 4xy-5y=-2 | | 10p+15p=5400 | | 3x+(229.84+y)=3039.14 | | 10x-7=101 | | 2x+45=3+7x-8 | | 5x+100=200 | | 2(s+3)=21 | | 5p^2-36p=32 | | (x+4)(6x^3+10x^2-9x+3)= | | 10x+17=3x | | -0.333333333333333x=-0.333333333333333x-0.5 | | 11.74=-log(x) | | 4x-8-2x+3=-10x+7+12x+5 | | 42s+s=8322 | | 4(4x-9)+9x= | | 9x+6(80)=7x+560 | | 6y=-2x | | 8x+9=9x+7 | | 6+3x+4x^2+2x^3=0 | | (6-8i)(6+8i)= | | 3(t-5)-t=7 | | 2x+2y=2809.30 | | 2(5x-6)=4[x-3x+30] | | 100x^2-21=110 |